2018
DOI: 10.2478/bjmg-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

ADRB2 gene polymorphisms and salbutamol responsiveness in Serbian children with asthma

Abstract: Inhaled β2 adrenergic receptor (β2-AR) agonists are the mainstay of asthma therapy. The β2-AR protein is encoded by the ADRB2 gene and variants within this gene can have significant consequences for modulating the response to asthma therapy. This cross-sectional study performed at the University Children’s Hospital in Belgrade, included 54 children with asthma. The subjects were genotyped for ADRB2 +46A>G (Arg16Gly, rs1042713) and +79C>G (Gln27Glu, rs 1042714) polymorphisms and the association with asthma seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…16,18,23 It encodes the β 2 adrenergic receptor, which is implicated in the bronchodilation process and is the biological target of β 2 adrenergic agonists. 19 In fact, in the reviewed period four candidate-gene studies have assessed the effect of the SNPs rs1042713 (arginine to glycine [Arg16Gly]) and rs1042714 (glutamic acid to glutamine [Glu27Gln]) on changes in lung function after SABA administration in European 24,25 and Egyptian 26,27 populations (Table 1). However, the results were not entirely consistent across studies.…”
Section: Candidate-gene Studies Of Saba Responsementioning
confidence: 99%
See 1 more Smart Citation
“…16,18,23 It encodes the β 2 adrenergic receptor, which is implicated in the bronchodilation process and is the biological target of β 2 adrenergic agonists. 19 In fact, in the reviewed period four candidate-gene studies have assessed the effect of the SNPs rs1042713 (arginine to glycine [Arg16Gly]) and rs1042714 (glutamic acid to glutamine [Glu27Gln]) on changes in lung function after SABA administration in European 24,25 and Egyptian 26,27 populations (Table 1). However, the results were not entirely consistent across studies.…”
Section: Candidate-gene Studies Of Saba Responsementioning
confidence: 99%
“…Scaparrotta et al 24 identified that G allele carriers for the SNP rs1042713 had a lower post-bronchodilator FEV 1 (β for the G allele: −0.244, p-value=0.02) while Jovicic et al 25 reported the opposite effect (p-value=0.044). Additionally, when both SNPs were analyzed as a haplotype, inconsistent results were also found since the AC haplotype was associated with a worse response to SABA in European children 25 (p-value=0.026) while in Egyptian children the same haplotype was associated with a better response (p-value=0.027). 27 All these inconsistencies might be due to the heterogeneity in statistical approaches.…”
Section: Candidate-gene Studies Of Saba Responsementioning
confidence: 99%
“…А за раніше отри маними даними, ризик розвитку БА у дорослих асоційований з поліморфізмом С79G, а також із поліморфізмом А46G [5,10,12,19,27]. У роботах деяких авторів також встановили асоціацію поліморфного варіанта С79G з ризи ком розвитку БА [18,24]. Хоча, з іншого боку, в низці досліджень таку закономірність не під твердили, і це може віддзеркалювати суттєві відмінності у формуванні досліджуваних груп, ключовим фактором якого можна вважати антропогенне навантаження довкілля забруд нювальними речовинами.…”
Section: результати дослідження та їх обговоренняunclassified
“…Таким чином, ці мононуклеотидні заміни можна розглядати як генетичні маркери тяжко сті перебігу БА [18,24].…”
Section: результати дослідження та їх обговоренняunclassified
See 1 more Smart Citation